2017
DOI: 10.1016/j.ymthe.2017.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Development and Mechanism of Small Activating RNA Targeting CEBPA, a Novel Therapeutic in Clinical Trials for Liver Cancer

Abstract: Small activating RNAs (saRNAs) are short double-stranded oligonucleotides that selectively increase gene transcription. Here, we describe the development of an saRNA that upregulates the transcription factor CCATT/enhancer binding protein alpha (CEBPA), investigate its mode of action, and describe its development into a clinical candidate. A bioinformatically directed nucleotide walk around the CEBPA gene identified an saRNA sequence that upregulates CEBPA mRNA 2.5-fold in human hepatocellular carcinoma cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 34 publications
2
76
0
Order By: Relevance
“…Searching for molecular mechanisms, we found that stabilization of key regulators of liver biology (C/EBPα, HNF4α, CUGBP1, Rb, and p53) under conditions of an HFD contributes to inhibition of steatosis. In agreement with this, several reports from Habib's group showed that the elevation of C/EBPα by a short‐activating RNA causes inhibition of liver cancer, metastasis, cirrhosis, fibrosis, and hepatosteatosis . In agreement with these observations, HFD‐treated GLKO mice and C/EBPα‐S193A mice have reduced C/EBPα and increased proliferation and spontaneously develop fibrosis and HCC, a situation observed in CUGBP1‐S302A mice.…”
Section: Discussionsupporting
confidence: 76%
“…Searching for molecular mechanisms, we found that stabilization of key regulators of liver biology (C/EBPα, HNF4α, CUGBP1, Rb, and p53) under conditions of an HFD contributes to inhibition of steatosis. In agreement with this, several reports from Habib's group showed that the elevation of C/EBPα by a short‐activating RNA causes inhibition of liver cancer, metastasis, cirrhosis, fibrosis, and hepatosteatosis . In agreement with these observations, HFD‐treated GLKO mice and C/EBPα‐S193A mice have reduced C/EBPα and increased proliferation and spontaneously develop fibrosis and HCC, a situation observed in CUGBP1‐S302A mice.…”
Section: Discussionsupporting
confidence: 76%
“…This saRNA activates the CEBPA mRNA and inhibits the growth of liver cancer cell lines in vitro. 97 Kim et al (2019) evaluated N-acetylgalactosamine (GalNAc) conjugation to antisense oligonucleotides (ASO) as a novel therapeutic approach that enhanced the antitumor activity in the HCC tumor model. ADP-ribosylation 4C (ARL4C) is a small GTP-binding protein that is highly expressed in primary HCC tumors.…”
Section: Strategies For Active Targeting To Livermentioning
confidence: 99%
“…C/EBPα saRNA (CEBPA-51): 30 sense, 5′-GCmG GmUC mAUmU GmUC mACmU GmGU CmUmU-3′ (special: 2′-OMe modified), and antisense, 5′-GAC CAG UGA CAA UGA CCG CmUmU-3′ (special: 2′-OMe modified 3′-UU overhang). Unrelated control siRNA: sense, 5′-GCG GAG ACA GCG ACG AAG AGC UCA UCA-3′, and antisense, 5′-UGA GCU CUU CGU CGC UGU CUC CGC UU-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Previous mechanistic studies have suggested that such short double-stranded RNAs that specifically target the promoter region of a gene can activate its transcription, a phenomenon termed transcription gene activation (TGA) which involves Argonaute-2 protein (Ago-2) activity. 21 , 30 The clinical observations revealed that intravenous (i.v.) administration of MTL-CEBPA induced an increase in CEBPA mRNA in white blood cells (WBCs) and a doubling of neutrophils within 24 h of dosing.…”
Section: Introductionmentioning
confidence: 99%